VD_FINDINFO HC / 2011 / 644 vom 21. September 2011 - VD Tribunal cantonal (2011)
CERTIFICAT D'HÉRITIER, RÉPUDIATIONDROIT SUCCESSORAL, DÉLAI, PROLONGATION | 570 al. 2 CC, 576 CC, 248 CPC (CH), 109 al. 3 CDPJ